Iraq Crude Oil Exports – January, February, March 2019 - SOMO, Ministry of Oil / Oil Marketing Company (Journal of Petroleum Research and Studies, 2020)
Table 1. Iraq Crude Oil Exports – January 2019 Table 2. Iraq Crude Oil Exports – February 2019 Table 3. Iraq Crude Oil Exports – March 2019